Chemical, rheological and sensory characteristics of wheat bread enriched with chia (Salvia hispanica L.) seed gum - Rawdah M. Al-Ali; Orass T. Al-Ibresam; Sawsan A. Al-Hilifi; Anka Trajkovska Petkoska; Sameh A. Korma (Future Foods)
Bread is a staple food in many countries worldwide. The aim of this study is the presentation of a novel type of bread prepared of wheat flour and extract of chia seed gum (CSG). The CSG was included in the wheat flour mixture in a concentration from 2 to 10%. The flour mixture was characterized by its rheological properties through amylography, farinography, and extensography tests. The bread was also subjected to texture, color, and tactile analysis. The highest grades of the bread in terms of appearance, flavor, aroma, texture, and color were shown for flour mixture that contained 10% of CSG (p < 0.05); namely, this wheat mixture showed an improved value of volume, specific size, external and internal characteristics of bread.